Effect of GTAW current variation on the mechanical properties and microstructure of Al-6061/Al-7075 dissimilar welds - Surya Dharma; Rahmawaty Rahmawaty; Rihat Sebayang; Yetti Meuthia Hasibuan; Syita Nabila Tazkia (Politeknik Negeri Lhokseumawe, 2026)
Aluminum and its alloys serve as foundational materials in the manufacturing industry, particularly in the aerospace, marine, and automotive sectors. While dissimilar welding is one of aluminum alloys’ most widely used joining techniques. This study assesses the impact of different welding currents (140 A, 150 A, and 160 A) on the Gas Tungsten Arc Welding (GTAW) of dissimilar Al-6061 and Al-7075 in terms of the mechanical properties (tensile strength and hardness) and microstructure of the welds. Tensile testing showed that a maximum tensile strength of 42.83 N/mm² was recorded at a welding current of 160 A, while a minimum strength of 22.66 N/mm² was seen at 140 A. All tensile specimens exhibiting failure also showed complete fracture within the weld zone, which suggests that the weld region is the predominant failure location. Vickers microhardness testing indicated the Al-6061 base material exhibited the most excellent hardness of 111.2 VHN (160 A) and decreased in the Heat-Affected Zone (HAZ) to 54.7 VHN in the weld metal. Moreover, hardness values averaged higher at 150 A compared to 140 A and 160 A. Microstructural examination at 500× revealed two main constituents in the weld joint: an aluminum solid solution (white) and the Mg2Si compound (black), which plays a significant role in the mechanical properties of the weld. The result of the study demonstrates the importance of adjusting welding parameters, particularly current strength, to attain the desired mechanical properties and ensure the structural integrity of various welded aluminum alloys.